Comparison of MIB-1 proliferation index with S-phase fraction in human breast carcinomas - Ellis, P A; Makris, A; Burton, S A; Titley, J; Ormerod, M G; Salter, J; Powles, T J; Smith, I E; Dowsett, M (British journal of cancer, 1996)
The MIB-1 antibody has been raised against recombinant parts of the Ki-67 antigen and, unlike Ki-67, has wider application to routinely fixed specimens. The aim of this study was to compare the usefulness of MIB-1 with S-phase fraction (SPF) as a measure of proliferation. A total of 75 patients with operable breast cancer were studied, 44 (median age 56 years) before any treatment and 31 (median age 68 years) after primary medical hormonal therapy. Sections from formalin-fixed paraffin-embedded tissue were stained with the MIB-1 antibody and a percentage score of positively stained cells obtained. SPF was measured by flow cytometry in fine-needle aspiration samples taken from the same lesion in each patient. Median MIB-1 score was 9% and median SPF was 11.1%. A close correlation was found between MIB-1 score and SPF (rho=0.59, P<0.0001). There was a difference in the strength of the correlation found between the no treatment group and the treatment group, however, 95% confidence intervals for the rho values overlapped, indicating that there was no significant statistical difference. When analysed for ploidy status a correlation was found only in aneuploid tumours. MIB-1 immunostaining can be used as an effective method of assessing proliferation in human breast carcinomas. This can be done using simple, widely available technology and provides the opportunity to perform large-scale retrospective analyses of archival materials.